Effectiveness of Intensive Short-Term Dynamic Psychotherapy on Perceived Stress in Patients with Hypertension - Hashemvarzi , MahmoudReza; Ghazanfari , Ahmad (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study was conducted to examine the effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) on perceived stress in patients diagnosed with hypertension. Materials and Methods: This study was an applied research project using a quasi-experimental design with pre-test and post-test and a control group. The research population included all patients with hypertension who visited comprehensive health service centers in Sari County in 2023. The research sample consisted of 45 individuals diagnosed with hypertension, selected through purposive sampling and randomly assigned to experimental and control groups. The Perceived Stress Scale developed by Cohen et al. (1983) and an 11-session protocol of Intensive Short-Term Dynamic Psychotherapy were used for data collection. Ethical considerations were fully observed. Data analysis was performed using SPSS version 26. Findings: The results of the study indicated that Intensive Short-Term Dynamic Psychotherapy approaches significantly reduce perceived stress in patients with hypertension (p<0.01). Conclusion: Given the increasing prevalence of hypertension, the necessity of implementing effective psychological interventions in this domain is evident. Based on the findings of this study, providing ISTDP training programs for professionals and medical assistants who interact with hypertensive patients may enhance the quality of care and improve patient outcomes.